Advances in mitophagy and mitochondrial apoptosis pathway-related drugs in glioblastoma treatment - Li, Weiping; Xu, Xia (Frontiers in Pharmacology, 2023)
Glioblastoma (GBM) is the most common malignant tumor of the central nervous system (CNS). It is a leading cause of death among patients with intracranial malignant tumors. GBM exhibits intra-and inter-tumor heterogeneity, leading to drug resistance and eventual tumor recurrence. Conventional treatments for GBM include maximum surgical resection of glioma tissue, temozolomide administration, and radiotherapy, but these methods do not effectively halt cancer progression. Therefore, development of novel methods for the treatment of GBM and identification of new therapeutic targets are urgently required. In recent years, studies have shown that drugs related to mitophagy and mitochondrial apoptosis pathways can promote the death of glioblastoma cells by inducing mitochondrial damage, impairing adenosine triphosphate (ATP) synthesis, and depleting large amounts of ATP. Some studies have also shown that modern nano-drug delivery technology targeting mitochondria can achieve better drug release and deeper tissue penetration,suggesting that mitochondria could be a new target for intervention and therapy. The combination of drugs targeting mitochondrial apoptosis and autophagy pathways with nanotechnology is a promising novel approach for treating GBM.This article reviews the current status of drug therapy for GBM, drugs targeting mitophagy and mitochondrial apoptosis pathways, the potential of mitochondria as a new target for GBM treatment, the latest developments pertaining to GBM treatment,and promising directions for future research.